The multifaceted role of macrophages in kidney physiology and diseases - Ma, Yiqi; Yang, Fengning; Yang, Jingjuan; Wang, Kewu; Hu, Jibo; Wu, Qian (Frontiers in Immunology, 2025)
Macrophages are highly plastic and heterogeneous innate immune cells that play pivotal roles in kidney development, kidney functions maintenance, immune surveillance, injury, repair, fibrosis and so on. Our understanding of embryonic derived and bone marrow–derived macrophages has evolved beyond the classical M1/M2 polarization paradigm, shifting toward a more nuanced investigation of macrophage subpopulations through the lens of functional specialization and tissue-specific adaptation. Recent advancements in single-cell and spatial transcriptomics have elucidated the diversity of kidney macrophages, revealing their critical contribution to kidney physiology and pathology. In acute kidney injury, macrophages orchestrate inflammatory cascades via cytokine secretion and inflammasome activation, whereas during the reparative phase, they promote tissue regeneration through anti-inflammatory pathways. However, persistent or dysregulated macrophage activation can lead to maladaptive repair and progression to chronic kidney disease characterized by kidney fibrosis. Therapeutically, targeting macrophage polarization, recruitment and macrophage-based adoptive cell therapy has emerged as a promising strategy for modulating kidney inflammation and fibrosis. This review delineates the multifaceted roles of diverse macrophage subsets in kidney physiology and pathology, while highlighting emerging therapeutic avenues and the translational challenges associated with macrophage-targeted interventions.